Systematic Literature Review: Pengalaman Belajar Kimia Organik yang Menyenangkan dengan Game Edukasi - Clarysa Satari; Wiji Wiji; Tuszie Widhiyanti; Sri Mulyani (Postgraduate, University of Mataram, 2024)
This article examines organic chemistry educational games developed between 2017-2023. The purpose of this study is to find out the types of educational games that are most developed, organic chemistry materials that have been developed in the form of educational games, and the positive impact of educational games in studying organic chemistry. The method used in this study is a systematic literature review. The systematic literature review is carried out in three stages, namely the planning stage, the implementation stage, and the reporting stage. Based on the results of the study, 38 articles were obtained by the criteria and further analysis was carried out. The results of the analysis show that organic chemistry educational games are developed with various types of games both in digital and non-digital forms. The most developed organic chemistry educational games are strategy video games and card games. The most developed material in the form of educational games is the molecular structure of organic compounds which is shown to deepen students' understanding in organic chemistry courses.